REPUTASI UNIVERSITAS MUHAMMADIYAH SURAKARTA (Studi Deskriptif Kuantitatif Terhadap Reputasi Universitas Muhammadiyah Surakarta Dalam Persepsi Mahasiswa dan Mahasiswi UMS) - SAKSONO, MEIKA YOGO (2011)
Muhammadiyah University of Surakarta is the major university which has a great vision to be world class university. To reach that dream the leader should know how stakeholders look at the reputation of his organization to identify the effectiveness of corporate communication. He also has to know the building block of reputation which the organization has because very good reputation can make competitive advantage for the company than the competitor and bad reputation is dangerous for the organization sustainability. The aim of this research is measuring reputation of Muhammadiyah University of Surakarta (UMS) in the perception of students as internal stakeholders. The researcher was using elements such as quality of service, quality of management, financial soundness, workplace environment, corporate social responsibility, emotional appeal and corporate ethics which suggested by Karakose (2008) to analyze reputation. Data was acquired from quitionaires that was obtained from 392 students of UMS as respondents. Then quantitative descriptive and Kolmogorov Smirnov were being used to analyze the data. The result of this study show that UMS has good enough reputation. In managerial implication, this research gives suggestion that UMS need to put more attention in dimension quality of service, mainly from tangibility aspect and also dimension of CSR because total mean of it was very low than other dimensions.